Optimizing Ergonomic Evaluation of Heavy Workload in Coffee Roasting to Reduce Operator Injury Risks: A Case Study using Cardiovascular Load, Rula, And Reba Methods - Yudha Arya Koeswara; Devi Maulida Rahmah (Universitas Darussalam Gontor, 2025)
Coffee production in Indonesia continues to grow along with the increasing demand for specialty coffee. One of the crucial stages in coffee processing is the roasting process, which requires close attention to the physical load and work posture of workers. This study evaluates the ergonomic risks associated with the coffee roasting process at Kedai Koffie Tandjoeng, a small-scale coffee business in Sumedang, Indonesia. Despite operating since 2015, the roasting process had never undergone a structured ergonomic assessment, even though the operator reported frequent discomfort, especially in the upper limbs and lower back. To assess these risks, this study used a combination of Cardiovascular Load (CVL), Rapid Upper Limb Assessment (RULA), and Rapid Entire Body Assessment (REBA) methods. The CVL result of 39.14% indicated a light to moderate physical workload, suggesting the need for workload management to prevent long-term fatigue. The RULA score of 5 and REBA score of 4 revealed moderate ergonomic risks, particularly in the upper arms and wrists during the lifting and pouring stages. Based on these findings, four recommendations were proposed: ergonomic training, the use of assistive tools (e.g., step stools), structured rest periods, and workstation layout adjustments. This study contributes to ergonomic research in the context of micro and small enterprises by applying an integrated assessment approach to a previously unassessed but physically demanding process. The results provide a practical foundation for future ergonomic interventions to reduce injury risks in small-scale coffee production environments.